Evaluating the Antecedents of Digital Financial Utilization Among MSMEs in the Era of Technological Transformation - Sri Anjarwati; Ari Apriani; Magita Magita; Islamiah Kamil; Januar Khaled; Yolifiandri Yolifiandri; Fauzan Taufiq Madini (SEAN Institute, 2025)
This study aims to evaluate the antecedent factors influencing digital financial utilization among Micro, Small, and Medium Enterprises (MSMEs) in the era of technological transformation. The study examines the influence of system quality, information quality, perceived usefulness, and perceived ease of use on the actual use of the Financial Information Recording Application System (SIAPIK). A quantitative research approach was employed using Structural Equation Modeling (SEM) with WarpPLS software. Data were collected through questionnaires distributed to MSME owners utilizing SIAPIK applications. The findings indicate that system quality and information quality positively and significantly influence perceived ease of use and perceived usefulness. Furthermore, perceived ease of use and perceived usefulness positively affect the actual use of SIAPIK applications. These results demonstrate that reliable systems, accurate information, and user-friendly digital financial applications encourage MSMEs to adopt digital financial technology more effectively. The implementation of SIAPIK contributes to improving financial management efficiency, operational effectiveness, and MSME sustainability in the digital transformation era.